The water-food-energy nexus power, politics and justice - Allouche, Jeremy; Gyawali, Dipak; Middleton, Carl (Abingdon, Oxon Routledge, 2019)
"The world of development thinkers and practitioners is abuzz with a new lexicon: the idea of "the nexus" between water, food, and energy which is intuitively compelling. It promises better integration of multiple sectoral elements, a better transition to greener economies, and sustainable development. However, there appears to be little agreement on its precise meaning, whether it only complements existing environmental governance approaches or how it can be enhanced in national contexts. One current approach to the nexus treats it as a risk and security matter while another treats it within economic rationality addressing externalities across sector. A third perspective acknowledges it as a fundamentally political process requiring negotiation amongst different actors with distinct perceptions, interests, and practices. This perspective highlights the fact that technical solutions for improving coherence within the nexus may have unintended and negative impacts in other policy areas, such as poverty alleviation and education. The Water-Food-Energy Nexus: Power, Politics and Justice lays out the managerial-technical definitions of the nexus and challenges these conceptions by bringing to the forefront the politics of the nexus, around two key dimensions - a dynamic understanding of water-food-energy systems, and a normative positioning around nexus debates, in particular around social justice. The authors argue that a shift in nexus governance is required towards approaches where limits to control are acknowledged, and more reflexive/plural strategies adopted. This book will be of interest to academic researchers, policy makers, and practitioners in the fields of international development studies, environmental politics, and science and technology studies, as well as international relations" -- Back cover.
1. Introduction: Nexus and nexuses -- 2. A critique of the global hegemonic nexus narratives -- 3. Integration for whom? Learning from the past -- 4. The knowledge nexus and transdisciplinarity -- 5. Hybrid governance and grounding the nexus -- 6. Nexus rights and justice -- 7. Ethics and the nexus -- 8. Conclusion: ‘Democratising’ the nexus.
Includes bibliographical references and index.
CSSP-9710 donated by College of Social Sciences and Philosophy.
Keywords: Energy security; Food security; Sustainable development; Water security